Googling the US Electoral Cycle, 2004-2016: South African Insights - Bhaso Ndzendze (The Thinker)
The US electoral cycle is one of the most closely watched political events in the twenty-first century. Indeed, in each successive year, new records are broken for expenditures on advertising by the campaigns. The digital sphere has become the main arena in which the various campaigns reach out to potential voters. By one 2019 estimate, “spending for political ads will reach $10 billion, an increase of 59% from the 2016 election year when an estimated $6.3 billion was spent. This represents a potential 16.5% of total local broadcast TV advertising revenue for 2020. Digital media is forecast for 21% of political ads, cable TV 14% and radio nearly 5%” (Adgate, 2019). This disproportional share for digital spending is indicative of what scholars have termed as the rise of computational politics, defined by one study as “the application of digital targeted-marketing technologies to election campaigns” (Chester and Montgomery, 2017: 1).